THE INFLUENCE OF CITY FACILITIES AND INFRASTRUCTURE ON RESIDENTIAL PREFERENCES IN BATANG KUIS DISTRICT - Syafri Benta; Cut Nuraini; Abdi Sugiarto (Bulletin of Engineering Science, Technology and Industry, 2025)
Batang Kuis District, located in Deli Serdang Regency, plays a strategic role as a buffer zone (urban fringe) for Medan City. With the increasing development of urban infrastructure and facilities, this area shows increasing potential as a residential location. This thesis aims to analyze the influence of urban infrastructure and facilities on the residential preferences of residents in Batang Kuis District. This study uses a quantitative approach with a survey method involving respondents from the local community (revealed preference) and outsiders (stated preference). The variables studied include urban facilities, infrastructure conditions, residential environments, and access to employment. The results show that urban facilities—especially trade, education, and health—are the most influential factors in residential choice. Infrastructure elements such as roads and clean water also play an important role, although their influence is at a lower level. Regression analysis shows that perceptions of urban facilities have a stronger and more significant influence on outsiders' desire to settle in Batang Kuis than infrastructure. Conversely, local residents prioritize aspects of affordability, environmental comfort, and proximity to family. These findings demonstrate the importance of a balanced regional development strategy that balances improvements to urban infrastructure and amenities to attract new residents and maintains comfort and affordability for existing residents.